EFFECTS OF DEEP TILLAGE OF COTTON ROWS ON COTTON YIELD (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Due to the belief that "the more cotton is grown between rows, the better the cultivation (chisel)", the deeper the softening of the rows will continue during the flowering period.